A Method for Quantification of Epithelium Colonization Capacity by Pathogenic Bacteria - Pedersen, Rune M.; Grønnemose, Rasmus B.; Stærk, Kristian; Asferg, Cecilie A.; Andersen, Thea B.; Kolmos, Hans J.; Møller-Jensen, Jakob; Andersen, Thomas E. (Frontiers in Cellular and Infection Microbiology, 2018)
Most bacterial infections initiate at the mucosal epithelium lining the gastrointestinal, respiratory, and urogenital tracts. At these sites, bacterial pathogens must adhere and increase in numbers to effectively breach the outer barrier and invade the host. If the bacterium succeeds in reaching the bloodstream, effective dissemination again requires that bacteria in the blood, reestablish contact to distant endothelium sites and form secondary site foci. The infectious potential of bacteria is therefore closely linked to their ability to adhere to, colonize, and invade epithelial and endothelial surfaces. Measurement of bacterial adhesion to epithelial cells is therefore standard procedure in studies of bacterial virulence. Traditionally, such measurements have been conducted with microtiter plate cell cultures to which bacteria are added, followed by washing procedures and final quantification of retained bacteria by agar plating. This approach is fast and straightforward, but yields only a rough estimate of the adhesive properties of the bacteria upon contact, and little information on the ability of the bacterium to colonize these surfaces under relevant physiological conditions. Here, we present a method in which epithelia/endothelia are simulated by flow chamber-grown human cell layers, and infection is induced by seeding of pathogenic bacteria on these surfaces under conditions that simulate the physiological microenvironment. Quantification of bacterial adhesion and colonization of the cell layers is then performed by in situ time-lapse fluorescence microscopy and automatic detection of bacterial surface coverage. The method is demonstrated in three different infection models, simulating Staphylococcus aureus endothelial infection and Escherichia coli intestinal- and uroepithelial infection. The approach yields valuable information on the fitness of the bacterium to successfully adhere to and colonize epithelial surfaces and can be used to evaluate the influence of specific virulence genes, growth conditions, and antimicrobial treatment on this process.